Greening the vehicle fleet, how does South Africa's tax reforms affect new car sales - Mfundo Nkosi; Johane Dikgang; Dambala Kutela Gelo; Alain Pholo (ZBW - Leibniz Information Centre for Economics, 2021)
An increasing number of countries around the world have linked taxes with passenger vehicle carbon dioxide (CO2) emission rates. Policymakers use vehicle and fuel taxes to target and reduce transportation greenhouse gas emissions. In 2010, the South African government joined this group, linking taxes to passenger-vehicle CO2-emission rates by introducing the vehicle CO2 tax, to reduce the carbon output of the new vehicle fleet by incentivising the purchase of more fuel-efficient vehicles. However, there is little evidence of the relative efficacy of this measure in South Africa. Based on new-vehicle sales data from 2010 to 2012, single-group interrupted time-series analysis (ITSA) reveals that CO2 taxes reduced average carbon emissions only marginally. This prompted the vehicle-CO2 tax reforms of 2013. Based on subsequent new-vehicle sales data, from 2013 to 2018, we find that the reforms have led to significant CO2 reductions. Overall, CO2 taxes moved consumer preference to low-emission vehicles (i.e., vehicles in the band producing less than 120g/km), and discouraged the purchase of bigger, heavier and more powerful vehicles. They also had a great effect on average emissions; by 2018, average carbon emissions had declined by 21% compared to 2010, to 151g/km. Moreover, there is some evidence that the tax has affected the mix of new vehicles that vehicle manufacturers sell in the South African market, as the volume of low carbon intensity new vehicles increased significantly, to 31% of total sales in 2018 compared to 13% in 2010.
Keywords: H31; L62; Q41; Q54; R48; 330; CO2; emissions; taxes; vehicles